POLICE INTERACTION WITH MUSLIMS – LEGAL AND PRACTICAL ASPECTS - Boluža, Inese; Lipe, Evita (Border Security and Management, 2018)
Due to the geopolitical changes in the world, police officers have to understand culture and religion of Muslims which will promote a more secure environment and self-confidence about the legal and practical aspects of interaction with Muslims in Latvia. However, the most police officers have insufficient knowledge of Islam regarding law enforcement in dealing with Muslims. Muslims, who have arrived in the last decade, have had a negative experience with police in their country of origin, so, in some cases, immigrants may be afraid of police officers and refuse to cooperate with them.